Kajian Permeabilitas Dan Kadar Air Tanah Pada Tiga Tipe Penggunaan Lahan Di Gambesi Kota Ternate - Ali, Karlina; Sofyan, Adnan; Rachman, Idris Abd; Hasan, Asrul Dedy Ali (Cannarium, 2022)
Village in Ternate City has the potential to be developed as an agricultural area because the soil type is Inceptisol which is suitable for agriculture. The ability of the soil to pass water, or what is commonly called soil permeability, is one of the important components for agricultural land management. Soil structure and texture as well as other organic elements play a role in increasing the rate of soil permeability. This study aims to understand soil permeability and soil water content in Gambesi. Samples were taken at a depth of 0-20 cm (Layer I) and 20-40 cm (Layer II) on three types of land use: residential areas, mixed dry land, and clove and nutmeg plantations. Soil sampling technique used purposive random sampling method. Identification of soil properties in the field is carried out using drill identification techniques, sample rings and profiling. Parameters observed were permeability, percent soil moisture content, specific gravity, particle density and soil texture. The results showed that the soil in each layer and type of land use had a variable permeability rate of 0.63-1.91 cm/hour, with a soil moisture content of 21.6-30.43%, a density of 1.01-1.91 cm. 1.23 gram/cm3, particle density of 2.0-2.27 gram/cm3, and porosity of 39.40-55.41%. The soil texture is sandy loam and sandy clay loam. The rate of soil permeability based on land use type has a rather slow permeability class, while the soil water content is at a permanent wilting point condition.Keywords: Bulk density, particle density, porosity, soil permeability, and soil water content